The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1136/bmj.38625.685706.ae
|View full text |Cite
|
Sign up to set email alerts
|

Preterm birth in twins after subfertility treatment: population based cohort study

Abstract: Objectives To assess gestational length and prevalence of preterm birth among medically and naturally conceived twins; to establish the role of zygosity and chorionicity in assessing gestational length in twins born after subfertility treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
4
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 23 publications
3
51
4
3
Order By: Relevance
“…Mode of conception influences the risk of preterm birth (Verstraelen et al, 2005), but not weight given a gestational time (Gielen et al, 2007). Therefore we did not perform different curves for twins who were naturally conceived and twins who were born after subfertility treatment.…”
Section: Figurementioning
confidence: 99%
“…Mode of conception influences the risk of preterm birth (Verstraelen et al, 2005), but not weight given a gestational time (Gielen et al, 2007). Therefore we did not perform different curves for twins who were naturally conceived and twins who were born after subfertility treatment.…”
Section: Figurementioning
confidence: 99%
“…Another study by Morcel et al found that ART resulted in lower-risk pregnancies compared to pregnancies conceived by ovulation induction (OI) [24]. There have been studies showing that subfertility, and not ART itself, actually has a bigger influence on the adverse outcomes in patients undergoing ART [25]. The risk of significant neurodevelopmental or behavioral adverse outcomes at two-year [26] or fiveyear [27][28] follow-ups appears to be minimal.…”
Section: Discussionmentioning
confidence: 99%
“…Previous results have indicated that this could not be the case (Delbaere et al, 2007;Loos et al, 2001d;Verstraelen et al, 2005). Comparison of DC-MZ, MC-MZ, and DZ twins will allow to evaluate the degree of gene-environment interactions as the prenatal environment is concerned.…”
Section: Discussionmentioning
confidence: 99%
“…The observed risks associated with assisted reproduction are dampening down by predominantly dizygotic twinning following assisted reproduction and by differential maternal characteristics (Verstraelen et al, 2005).…”
Section: A Summary Of Major Findingsmentioning
confidence: 99%